Ergonomic and biomechanical evaluation of the use of computers, tablets and smart phones by children. A pilot study (2017)
The use of technological devices has widespread around the world. It is known that inappropriate or prolonged use of electronic devices can cause musculoskeletal discomfort or even illness. However, there are not many studies that evaluate the associated risks on the children’s health. This paper describes a pilot ergonomic study for the analysis of the postures of a five-year old girl while using a laptop computer, a tablet, and a smart phone. The analysis was done using the software Delmia to generate 3D models of the child body, that were created based on photographs. We considered five positions: desk sitting, sitting cross legged, lying supine, lying prone and standing. The results suggest that the safest positions are sitting on a desk and standing, and the greatest risk is in the area of necktrunk. However, further investigation is needed to validate the musculoskeletal risks associated to the use of electronic devices by children. © Springer Nature Singapore Pte Ltd. 2017.